2016
DOI: 10.1007/s00430-016-0469-7
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 replication in central nervous system increases over time on only protease inhibitor therapy

Abstract: There are concerns about central nervous system (CNS)-replication of HIV-1 in patients on boosted protease inhibitors. Purpose of this study was to compare HIV-1 viral loads (VLs) from patients treated with only boosted dual protease inhibitor (bdPI), versus combination antiretroviral therapy (cART group), containing two nucleoside analogue reverse transcriptase inhibitors (NRTI) and a third partner. All patients from a large German HIV-treatment cohort with available medication, clinical and demographic data,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Mono ATV/r study described 15% risk of CSFVE at 24 weeks, and all three patients with escape had suppressed plasma HIV RNA. Another study also described early CSFVE during PI only therapy (Donath et al 2016). This raises the importance of backbone NRTI in controlling viral replication in CNS compartment (Vernazza et al 2007).…”
Section: Discussionmentioning
confidence: 98%
“…Mono ATV/r study described 15% risk of CSFVE at 24 weeks, and all three patients with escape had suppressed plasma HIV RNA. Another study also described early CSFVE during PI only therapy (Donath et al 2016). This raises the importance of backbone NRTI in controlling viral replication in CNS compartment (Vernazza et al 2007).…”
Section: Discussionmentioning
confidence: 98%
“…Studies have shown a higher CSF HIV replication in patients taking double-boosted PI regimens, supporting possible functional monotherapy in the CNS. [ 38 ] As PIs are substrates for drug efflux transporters that are expressed on brain microvascular endothelial cells and ependymal cells of choroid plexus, their concentrations in CNS can be subtherapeutic. [ 39 ] These results supports the inference that shifting to a PI such as darunavir that has better CNS penetration than atazanavir [ 40 ] and superior efficacy against triple-class resistant virus than lopinavir [ 41 ] may reduce the risk of CSF/plasma HIV-1 RNA discordance.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, it has been shown that ART itself can influence the existing reservoir. In particular, boosted dual protease inhibitor regimens have a poor ability to penetrate the blood–brain barrier, which can result in residual HIV replication in the CNS [9]. Thus, there is an urgent need for novel parameters describing ongoing replication in certain compartments and tissues, i.e., sanctuary sites of replication, as well as therapeutical possibilities to intervent or improve the possibility to penetrate the replication sites.…”
Section: Discussionmentioning
confidence: 99%
“…Since the rate of viral decay after ART initiation is related to the half-life of the virus producing cells [6], a prolonged decline might be associated with the presence of long-lived productively infected cells like macrophages and latently infected CD4 + T cells, which can be stimulated to produce virus upon interaction with specific antigens [1]. Furthermore, cells present in sanctuary sites, which are difficult to target by the immune response and by drugs, were shown to contribute to the HIV-1 RNA decline [1, 2, 79]. Recently, it has been shown that persistent HIV-1 replication can maintain in tissue reservoirs during therapy and that HIV-1 can continue to replicate and refill those viral reservoirs despite effective ART [8].…”
Section: Introductionmentioning
confidence: 99%